Faktor Penentu Niat Menggunakan Paylater Dengan Kepercayaan Sebagai Variabel Moderasi - Ahmad Afandi; Dia Purnama Sari; Annessa Fadhillah; Nando Farizal; Muhammad Arif (Program Study Islamic Banking, Faculty of Economics and Bussiness Islam, State Islamic Institute of Manado (IAIN) Manado, 2022)
The purpose of this study is to measure effort expectancy, habit, price value, hedonic motivation, and social influence on the intention to use paylater with trust as a moderating variable. This research is a descriptive quantitative type and data collection method using a questionnaire. This research involved a total of 100 respondents who were all residents of North Sumatra. Structural Equation Model (SEM) and SmartPLS are used in data analysis techniques to test hypotheses and identify factors that influence people's intention to use Paylater. The research findings show that the social influence variable has a positive and significant effect on the intention to use Paylater. Meanwhile, effort expectancy, habit, price value, and hedonic motivation have no effect on the intention to use Paylater. Then the trust variable cannot moderate effort expectancy, habit, price value, hedonic motivation and social influence on the intention to use Paylater, maybe because Paylater has several risks so that trust cannot moderate these variables. This proves that the people of North Sumatra who use paylater are due to social influences without thinking about anything that is at risk for the user. It is hoped that the results of this study can be used as a reference for prospective Paylater users in using them and become information for related institutions. This research is expected to be information in developing further research by adding risk variables that influence the intention to use Paylater.